2018
DOI: 10.1097/ico.0000000000001697
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Acuity Outcomes Between Nanothin Descemet Stripping Automated Endothelial Keratoplasty and Descemet Membrane Endothelial Keratoplasty

Abstract: Compared with DMEK, NT-DSAEK provides comparable visual outcomes and complications rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 33 publications
2
55
0
Order By: Relevance
“…While Bhandari et al [21] and Chamberlain et al [17] found better visual outcomes after DMEK compared to UT-DSAEK, Tourabaly et al [22] found similar BCVA between DMEK, UT-DSAEK and NT-DSAEK and Kurji et al [16] between DMEK and NT-DSAEK.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While Bhandari et al [21] and Chamberlain et al [17] found better visual outcomes after DMEK compared to UT-DSAEK, Tourabaly et al [22] found similar BCVA between DMEK, UT-DSAEK and NT-DSAEK and Kurji et al [16] between DMEK and NT-DSAEK.…”
Section: Discussionmentioning
confidence: 99%
“…DMEK and DSAEK are the two most widely performed endokeratoplasty techniques for the treatment of endothelial dysfunctions. Even though there is evidence that DMEK may give equal or better results than "conventional" DSAEK (with grafts thicker than 130 μm and a faster recovery time [1,[5][6][7][8][9][10], few studies have directly compared the visual outcomes between UT-DSAEK and DMEK [16,17,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of modified techniques with both automated and manual microkeratomes has enabled surgeons to perform ultra-thin DSAEK with faster visual recovery and superior visual outcomes 2–4. Moreover, DSAEK has the advantage of an easier learning curve and less tissue loss during donor preparation than DMEK 5.…”
Section: Introductionmentioning
confidence: 99%
“…Newer modifications to DSAEK have created thinner grafts. Ultrathin DSAEK (UT-DSAEK) (60-90 lm grafts) and nanothin DSAEK (NT-DSAEK) (grafts 50 lm or thinner) have been shown to have improved visual outcomes with faster visual recovery than standard DSAEK [17][18][19][20].…”
Section: Descemet Stripping Automated Endothelial Keratoplastymentioning
confidence: 99%